Synovial Hemangioma of The Ankle Joint - A Rare Entity - Iqbal, Sahar (International Journal of Pathology, 2019)
Synovial hemangioma is a rare benign tumor of vascular origin usually effecting joint spaces and tendon sheaths. Patient may present with non-traumatic pain and swelling, sometimes giving the clinical impression of bursitis. Rarity of the condition, vague clinical symptoms and non-specific radiological findings may lead to delayed diagnosis. We present a case of synovial hemangioma of ankle joint which is quite an infrequent site for this lesion.Synovial hemangioma is a rare benign tumor of vascular origin usually effecting joint spaces and tendon sheaths. Patient may present with non-traumatic pain and swelling, sometimes giving the clinical impression of bursitis. Rarity of the condition, vague clinical symptoms and non-specific radiological findings may lead to delayed diagnosis. We present a case of synovial hemangioma of ankle joint which is quite an infrequent site for this lesion.